2017
DOI: 10.1016/j.jveb.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Animal olfactory detection of human diseases: Guidelines and systematic review

Abstract: Animal olfactory detection of human diseases has attracted an increasing amount of interest from researchers in recent years. Because of the inconsistent findings reported in this body of research and the complexity of scent detection research, it is difficult to ascertain the potential value of animal detectors in operational diagnostic algorithms. We have outlined key factors associated with successful training and evaluation of animals for operational disease detection and, using these key factors as points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 68 publications
0
87
0
Order By: Relevance
“…Several factors can influence a dog-handler team´s accuracy rate [32,49,53]. Working dogs have been stated to have increased success when it comes to careful selection in relation to breed and personality traits as e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several factors can influence a dog-handler team´s accuracy rate [32,49,53]. Working dogs have been stated to have increased success when it comes to careful selection in relation to breed and personality traits as e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Faecal pellets from the ptarmigans were collected in the field for the genetic study and directly placed in plastic jars (Nalgene, 15 x 38 mm or 30 x 43 mm, Thermo Scientific™, Norway). Later, they were taken out of the jars for seven days to dry and cross-contamination of the pellets was avoided by separating them by species and only interacting with them using sterilised equipment [32]. Time from sampling in the field, to when the drying process was initiated, could range from five hours to two weeks.…”
Section: Scent Donorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are also associated with some disadvantages, particularly those related to potential cuing (see Lit et al, 2011); subjectivity involved in the identification of the indication response and data collection in general; and the immediacy, accuracy, and reliability of reinforcer delivery. For these reasons, Edwards et al (2017) suggested that an optimal laboratory-based approach to scent-detection research and operations is fully automated. However, few, if any, automated solutions for applied scent-detection research with dogs have been described in the literature and no such apparatus is available commercially.…”
Section: Introductionmentioning
confidence: 99%